019 Metalloproteinases and foam-cell phenotypes in unstable atherosclerotic plaques. (22nd September 2015) - Jenkins, N P; Johnson, J L; Marx, N; Pasterkamp, G; Newby, A C
Abstract : Introduction: Matrix metalloproteinase (MMP) production from foam cell macrophages (FCMs) is implicated in atherosclerotic plaque formation and cap rupture leading to myocardial infarction. Recent work from our laboratory associated diverse patterns of MMP production with functional diversity of rabbit FCMs. In this study we investigated whether FCM populations expressing different MMPs and tissue inhibitor of MMPs (TIMPs) exist in human plaques and associate with histological measures of plaque instability. We also investigate whether lipid-lowering in rabbits and systemic treatment with a PPARγ agonist in humans alter the balance of FCM populations. Methods: Serial tissue sections were immunostained for CD68 to identify FCMs and for MMPs-2, -12 and -14, TIMP-3, CCR2, COX-2, and CD206 or non-immune controls. The percentage of FCMs positive for each protein was counted by blind analysis. We used 20 stable and 20 unstable human carotid endarterectomy specimens from the AtheroExpress biobank and 30 human coronary artery specimens from cadaveric donors. In addition, patients were randomised (n=12 per group) to receive either the PPARγ agonist rosiglitazone or placebo for 4 weeks before carotid endarterectomy. Aortic tissue was studied from New Zealand White rabbits fed a cholesterol-rich diet with a subgroup returned to normal chow. Results: Relationship to plaque vulnerability: A higher percentage of FCMs in unstable plaques stained for MMPs-2, -12 and -14 (Abstract 019 Figure 1 ) and markers of classical activation CCR2 and COX-2 than in stable plaques (Abstract 019 Table 1 ). A higher percentage of FCMs in stable plaques stained for TIMP-3 and a marker for alternative activation CD206 than in unstable plaques. A similar excess of MMP-14 staining in FCMs was observed in vulnerable human coronary lesions compared to stable lesions (Abstract 019 Figure 1 ). Reversal: The percentage of MMP-14 positive FCMs (83+7% and 74±5%) in plaques from rabbits fed cholesterol for 8 and 16 weeks declined to 49±4% in plaques from rabbits returned to a normal diet for the last 8 weeks (n=8 each, p<0.001). There were no significant differences in FCM expression profiles in plaques from patients treated with a PPARγ agonist compared to placebo. Conclusions: Populations of MMP positive, TIMP-3 negative FCMs were identified in vulnerable human carotid and coronary atherosclerotic plaques and associated with markers of classical activation. Conversely, TIMP3 positive FCMs expressing alternative activation markers associated with stable plaques. Our unpublished results also show that classically-activated macrophages express high levels of MMPs-2, -12, -14, and COX2 and low levels of TIMP-3 and CD206 in vitro. Lipid lowering in rabbits favourably altered MMP-14 expression. However, short PPARγ agonist treatment was ineffective. MMP positive FCMs may be useful to identify vulnerable plaques using imaging tools and are targets for plaque stabilising therapy.